Determination of Perfluorooctanoic Acids in Different Water Samples by Electrospray Extraction Ionization Tandem Mass Spectrometry - Hui-yu XING; Lan-fang CHEN; Fa-wang ZHAN; Xiao-wei FANG; Huan-wen CHEN (Zhipu Xuebao, 2024)
Water is a vital resource on the earth, serving as the foundation of life and playing a crucial role in our daily activities. Perfluorooctanoic acid (PFOA) is an organic compound, which poses a significant threat to the environment due to its persistence and bioaccumulation. PFOA exhibits various toxicities, including neurotoxicity, immunotoxicity, and carcinogenicity. It has been detected in worldwide of air and water samples, as it can easily move through different environmental media such as water, soil, and the atmosphere. The widespread distribution of PFOA in these media poses potential risks to both ecosystems and human health over the long term. Therefore, it is of utmost importance to develop a rapid detection method for accurately monitoring PFOA levels in water. In this study, the electrospray extraction ionization-tandem mass spectrometry (EESI-MS/MS) technique was utilized to directly and rapidly detect PFOA in tap water and river water. To achieve the highest ionization efficiency of PFOA in EESI-MS/MS across different water samples, the experimental parameters such as ion transfer tube temperature, spray voltage, electrospray solvent flow rate, and sample flow rate were optimized. The optimal conditions were temperature of 200 °C for the ion transfer tube, spray voltage of 2 kV, electrospray solvent flow rate of 4 µL/min, and sample flow rate of 6 µL/min. The experiments were conducted under negative ion mode with a mass scan range of m/z 50-500. Methanol solution was used as the electrospray solvent, and collision-induced dissociation (CID) was employed. The secondary characteristic fragment ion m/z 369 of m/z 413 for qualitative and quantitative analysis, enabling direct and rapid detection of PFOA in various water samples. The experimental results demonstrated good linearity of PFOA in the concentration range of 1-500 ng/L, with a linear correlation coefficient (R2) of 0.9976. The detection limit (LOD) of the proposed method is 0.57 ng/L, and the limit of quantification (LOQ) is 1.73 ng/L. The recovery rate ranges from 92.1% to 105.2%, with a relative standard deviation (RSD, n=6) of 1.89%-5.45%. In summary, this method has the advantages of high sensitivity, accuracy, and fast analysis speed, without the need of sample pretreatment. The established EESI-MS/MS method can be effectively applied for direct and rapid detection of PFOA in different water samples, showing promising prospects for monitoring environmental water pollutants. Moreover, it provides valuable references and technical means for the detection of other pollutants.